An X-Ray Counterpart of HESS J1427−608 Discovered with Suzaku - Fujinaga, Takahisa; Mori, Koji; Bamba, Aya; Kimura, Shoichi; Dotani, Tadayasu; Ozaki, Masanobu; Matsuta, Keiko; PÜHlhofer, Gerd; Uchiyama, Hideki; Hiraga, Junko S.; Matsumoto, Hironori; Terada, Yukikatsu (Publications of the Astronomical Society of Japan, 2013)
We report on the discovery of an X-ray counterpart of the unidentified very high-energy gamma-ray source HESS J1427 $-$ 608. In the sky field coincident with HESS J1427 $-$ 608, an extended source was found in the 2–8 keV band, and was designated as Suzaku J1427–6051. Its X-ray radial profile has an extension of $ σ$ $ =$ 0 $ .\!\!'$ 9 $ ±$ 0 $ .\!\!'$ 1 if approximated by a Gaussian. The spectrum was well fitted by an absorbed power-law with $ N_{\rm H}$ $ =$ (1.1 $ ±$ 0.3) $ ×$ 10 $ ^{23}$ cm $ ^{-2}$ , $ Γ$ $ =$ 3.1 $ ^{+0.6}_{-0.5}$ , and the unabsorbed flux $ F_{\rm X}$ $ =$ (9 $ ^{+4}_{-2}$ ) $ ×$ 10 $ ^{-13}$ erg s $ ^{-1}$ cm $ ^{-2}$ in the 2–10 keV band. Using XMM-Newton archive data, we found seven point sources in the Suzaku source region. However, because their total flux and absorbing column densities are more than an order of magnitude lower than those of Suzaku J1427–6051, we consider that they are unrelated to the Suzaku source. Thus, Suzaku J1427–6051 is considered to be a truly diffuse source and an X-ray counterpart of HESS J1427 $-$ 608. The possible nature of HESS J1427 $-$ 608 is discussed based on the observational properties.